The role of 18F-FDG PET/CT in evaluation of therapy effectiveness and prognosis of lymphomas - N. G. Chanchikova; V. I. Chernov; E. A. Dudnikova; E. A. Karlova; A. S. Savelyeva; O. A. Silkina; R. V. Zelchan; O. D. Bragin; A. A. Medvedeva; E. V. Berezneeva (Бюллетень сибирской медицины)
Aim. To determine the diagnostic value of positron emission tomography (PET)/computed tomography (CT) with F-18 fluorodeoxyglucose (18F-FDG) for monitoring the effectiveness and prognosis of lymphoma therapy.Materials and methods. Retrospective data of 18F-FDG PET/CT (before treatment (PET1), after two cycles (PET2), and after completion of chemotherapy (PET3)) in 30 people with lymphomas were analyzed.Results. A complete metabolic response in PET2 (PET2–) was observed in 21 patients (70%). In 9 patients in PET2–, a partial metabolic response (6 people), lack of metabolic response (2 people), or metabolic progression (1person) were detected. These patients comprised the PET2+ group.After chemotherapy, a complete metabolic response (PET3–) was diagnosed in 26 patients (87%). This effect was achieved in 21 patients (100%) with PET2– and in 5 patients (66%) with PET2+. Of the 9 patients in the PET2+ group, in 4 (44%) patients, a partial metabolic response or no metabolic response was diagnosed. Further monitoring of these patients showed that progression was diagnosed in 2 cases, and in 2 patients, further treatment resulted in complete remission. A two-year follow-up of patients revealed that remission was observed in 20 (67%) patients. The analysis of the results of PET2 showed that a relapse of the disease was observed in 6 (67%) PET2+ patients and remission was noted in 3 (33%) patients. In PET2– patients, a relapse was diagnosed in 4 (19%) persons, and remission was established in 17 (81%) patients.Conclusion. Early PET/CT with 18F-FDG allows to predict the effect of  lymphoma treatment. The method can be recommended for monitoring lymphoma therapy.